2009
DOI: 10.1002/msc.157
|View full text |Cite
|
Sign up to set email alerts
|

‘All singing from the same hymn sheet’: Healthcare professionals' perceptions of developing patient education material about the cardiovascular aspects of rheumatoid arthritis

Abstract: Although healthcare professionals agree that it is important to convey the increased CVD risk to patients with RA, there is concern they may be less proactive in promoting risk management strategies. There was uncertainty about the best time to discuss CVD with RA patients. Maintaining a close relationship between primary and secondary care was thought to be important, with all healthcare professionals 'singing from the same hymn sheet'. These findings can inform the development of novel education material to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2011
2011
2018
2018

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 42 publications
0
8
0
2
Order By: Relevance
“…Podiatrists have the skills and knowledge to assess and monitor patients' lower limb vascular status and are well placed to discuss the effect of smoking on lower limb health, such as the development of peripheral arterial disease, which is accelerated in people with RA [18,19]. Patient education for people with RA about cardiovascular disease has been recognised as being poorly promoted by health care professionals [20]. …”
Section: Discussionmentioning
confidence: 99%
“…Podiatrists have the skills and knowledge to assess and monitor patients' lower limb vascular status and are well placed to discuss the effect of smoking on lower limb health, such as the development of peripheral arterial disease, which is accelerated in people with RA [18,19]. Patient education for people with RA about cardiovascular disease has been recognised as being poorly promoted by health care professionals [20]. …”
Section: Discussionmentioning
confidence: 99%
“…This may have related to the fact that it ‘broke bad news’ about co‐morbid CVD associated with RA (John et al, ). The converse would be to adopt a more paternalistic view that patients could not cope with bad news (Coulter, ); however, this denies patients the opportunity to make informed decisions about their lifestyle (John et al, ). Certainly, the empowerment that respondents wrote about in the free text comments suggests that the information was appreciated and would be acted upon.…”
Section: Discussionmentioning
confidence: 99%
“…Mindful that the literature reports a potential incongruence between the information provided by health professionals and the information that patients request (Hirsh et al, ), it was felt important to have patient input both in the development of the leaflet and in its evaluation. Hence, qualitative research with stakeholders was performed, namely individual interviews with patients with RA and focus groups with relevant healthcare professionals (John et al, ). This revealed that patients were mostly unaware of the association between RA and CVD, but were interested in learning what could be done to address their risk, requesting ‘common sense’ advice, taking into account their RA (John et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…This includes not only patients, when education about relevant lifestyle modifications needs to be provided within the context of any physical and psychosocial constraints related to RA [47], but also health professionals. The excess CVD risk conferred by RA has been shown to be under-recognized and under-assessed in primary care [48 ]; appropriate education of both primary and secondary healthcare professionals is required so that a consistent message is given to the patient [49].…”
Section: Cardiovascular Disease Risk Management In Rheumatoid Arthritismentioning
confidence: 99%